Application of Grey-Taguchi method for optimizing acid leaching step in Zircon alkali fusion process - A. Yadollahi; K. Saberyan; M. Torab Mostaedi; A. Charkhi (مجله علوم و فنون هسته‌ای, 2020)
Alkali fusion with NaOH is the most commonly used method for the extraction of zirconium from zircon sand. In the alkali fusion process, the acid leaching step has a great influence on the zirconium recovery and purity of the final product. In this study, the Grey-Taguchi method was utilized to find the optimum conditions of the acid leaching process. In order to apply this method, acid type, acid concentration, leaching temperature, and liquid/solid ratio were selected as control factors with responses of zirconium recovery and R=Si/Zr ratio. The results demonstrated that the optimum condition for acid leaching requires 4 mol/L sulfuric acid with a liquid/solid ratio of 20 at 60 °C. Zirconium recovery and Si/Zr ratio (R) under these optimum conditions were 92.73% and 0.0018, respectively. Also, the silica content in the acid leaching solution was 30.94 ppm. The results of this research suggest facile, low price, and proper method comparing to the carbochlorination method for recovery of zirconium from zircon mineral.